Positive electrode active material, method for producing same, and non-aqueous electrolyte secondary battery

By replacing Mn into W and Mg in the positive electrode active material of the nonaqueous electrolyte secondary battery, a layered rock salt-type crystal structure with the composition formula of LiaNibMncWdMgeOf is formed, and the positive electrode active material is easily decomposed at high temperatures in the prior art and Co. The problem of high cost achieves high discharge capacity, excellent output characteristics and thermal stability, and reduces raw material costs.

CN119301773APending Publication Date: 2025-01-10AICHI STEEL CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202380043127.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-17
Filing Date
2023-06-02
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The positive electrode active substance of the existing nonaqueous electrolyte secondary battery is easily decomposed at high temperatures, and the raw material cost is high due to the presence of Co, and the thermal stability and output characteristics are insufficient.

Method used

The positive electrode active material with the composition formula of LiaNibMncWdMgeOf is used, where a~f satisfies 0.9

Benefits of technology

It achieves high discharge capacity, excellent output characteristics and thermal stability, while reducing raw material costs and avoiding cost risks caused by Co content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119301773A_ABST
    Figure CN119301773A_ABST
Patent Text Reader

Abstract

The positive electrode active material is configured so as to be usable in a non-aqueous electrolyte secondary battery. The positive electrode active material has a composition represented by the compositional formula LiaNibMncWdMgeOf (wherein a-f in the compositional formula satisfies the following relationship: 0.9 < a < 1.2, 0.45 < b < 0.6, 0.25 < c < 0.5, 0 < d < 0.06, 0 < e < 0.1, and 1.9 < f < 2.1), and has a layered rock salt crystal structure attributable to space group R-3m.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a positive electrode active material, a method for producing the same and a non-aqueous electrolyte secondary battery. Background Art

[0002] Non-aqueous electrolyte secondary batteries such as lithium-ion secondary batteries can easily increase energy density. In recent years, this property has been effectively utilized to use non-aqueous electrolyte secondary batteries in a wide range of applications, including small electronic devices such as mobile phones and notebook computers, and large electric drive devices such as electric vehicles and hybrid vehicles.

[0003] As a positive electrode active material of a non-aqueous electrolyte secondary battery, LiNi containing Li (lithium), Ni (nickel), Mn (manganese) and Co (cobalt) 0.33 Mn 0.33 Co 0.33 O2 (so-called NMC111), LiNi containing Li, Ni, Co and Al (aluminum) 0.8 Co 0.15 Al 0.05 O2 (so-called NCA) and the like have been put into practical use. However, there is a strong desire for positive electrode active materials with higher discharge capacity than these positive electrode active materials. In addition, since these positive electrode active materials contain Co, which is a rare element, there is a high risk of rising raw material costs due to various reasons such as changes in supply and demand.

[0004] As a positive electrode active material not containing Co, for example, Patent Document 1 describes a positive electrode active material for a non-aqueous electrolyte secondary battery, which contains a general formula Li a Ni b Mn 1-b W c A lithium transition metal composite oxide represented by O2 (wherein 1<a<1.2, 0.5≤b≤0.7, 0<c≤0.02). Prior art literature Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2012-43637 Summary of the invention Technical problem to be solved by the invention

[0006] When the positive electrode and the negative electrode of the non-aqueous electrolyte secondary battery are short-circuited for some reason, the temperature of the non-aqueous electrolyte secondary battery sometimes rises due to Joule heat. In addition, when the temperature of the non-aqueous electrolyte secondary battery rises excessively, it is possible to cause the decomposition of the positive electrode active material. From this point of view, it is desired that a positive electrode active material has higher thermal stability than the positive electrode active material described in Patent Document 1.

[0007] The present invention has been completed in view of this background, and its purpose is to provide a positive electrode active material that can reduce raw material costs, has a high discharge capacity, and is excellent in thermal stability and output characteristics, a method for producing the same, and a non-aqueous electrolyte secondary battery using the same. Technical solutions for solving technical problems

[0008] One embodiment of the present invention is a positive electrode active material for a non-aqueous electrolyte secondary battery, wherein: The positive electrode active material has a composition formula of Li a Ni b Mn c W d Mg e O f (wherein a to f in the composition formula satisfy the following relationships: 0.9<a<1.2, 0.45<b<0.6, 0.25<c<0.5, 0<d<0.06, 0<e<0.1, 1.9<f<2.1) and The positive electrode active material has a layered rock salt type crystal structure attributable to space group R-3m.

[0009] Another embodiment of the present invention is a non-aqueous electrolyte secondary battery having a positive electrode, a negative electrode, and a non-aqueous electrolyte, wherein: The positive electrode includes the positive electrode active material of the embodiment described above. Effects of the Invention

[0010] The positive electrode active material has the specific composition and crystal structure. Since the positive electrode active material does not contain Co, the risk of rising raw material costs can be reduced. In addition, in the positive electrode active material, a portion of Mn in the Li-Ni-Mn positive electrode active material is replaced by W and Mg. In this way, by adding W and Mg to the Li-Ni-Mn positive electrode active material, the thermal stability of the positive electrode active material can be improved while ensuring high discharge capacity and excellent output characteristics.

[0011] Therefore, the positive electrode active material has a high discharge capacity, is excellent in thermal stability and output characteristics, and can easily reduce the raw material cost.

[0012] In addition, the nonaqueous electrolyte secondary battery of the above embodiment has a positive electrode containing the specific positive electrode active material. Therefore, the nonaqueous electrolyte secondary battery can easily reduce the cost of raw materials, has a high discharge capacity, and is excellent in thermal stability and output characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 1 is a development view showing the internal structure of a secondary battery in the embodiment. DETAILED DESCRIPTION

[0014] (Positive electrode active material) The positive electrode active material has a composition formula of Li a Ni b Mn c W d Mg e O f (wherein a to f in the composition formula satisfy the following relationships: 0.9<a<1.2, 0.45<b<0.6, 0.25<c<0.5, 0<d<0.06, 0<e<0.1, 1.9<f<2.1)

[0015] The value of a in the composition formula, that is, the molar ratio of Li to the total number of moles of Li, Ni, Mn, W, Mg and O is greater than 0.9 and less than 1.2. As a result, the specific crystal structure is easily maintained during charge and discharge, and a diffusion path of lithium ions can be fully formed in the positive electrode active material. As a result, the discharge capacity and output characteristics of the positive electrode active material can be improved.

[0016] When the value of a in the composition formula is less than 0.9, in the lattice of the positive electrode active material, a phenomenon called cation mixing, in which lithium ion sites are replaced by transition metal ions, is likely to occur. Therefore, in this case, it is difficult to fully form a diffusion path for lithium ions in the positive electrode active material, which may lead to a reduction in discharge capacity and output characteristics. In addition, when the value of a in the composition formula is more than 1.2, a lithium-excess layered rock salt type crystal structure belonging to the space group C2 / m is easily formed in the positive electrode active material, which may lead to a reduction in output characteristics.

[0017] The value of d in the composition formula, that is, the molar ratio of W to the total number of moles of Li, Ni, Mn, W, Mg and O, is greater than 0 and less than 0.06. In addition, the value of e in the composition formula, that is, the molar ratio of Mg to the total number of moles of Li, Ni, Mn, W, Mg and O, is greater than 0 and less than 0.1. By adding both W and Mg to the positive electrode active material and setting the content of these elements to the specific range, thermal stability can be improved without damaging the discharge capacity and output characteristics of the positive electrode active material.

[0018] When the value of d in the composition formula is 0, that is, when only Mg of W and Mg is added to the positive electrode active material, the discharge capacity and output characteristics may be reduced. From the viewpoint of more reliably obtaining the effect of the combined use of W and Mg, the value of d in the composition formula is preferably 0.005 or more, and more preferably 0.01 or more.

[0019] When the value of d in the composition formula is 0.06 or more, a crystal phase having a crystal structure other than the specific layered rock salt type crystal structure is easily formed in the positive electrode active material, which may lead to a decrease in discharge capacity and thermal stability.

[0020] In addition, when the value of e in the composition formula is 0, that is, when only W of W and Mg is added to the positive electrode active material, the thermal stability of the positive electrode active material may be reduced. From the viewpoint of more reliably obtaining the effect brought about by the combined use of W and Mg, the value of e in the composition formula is preferably 0.005 or more, and more preferably 0.01 or more.

[0021] On the other hand, when the value of e in the composition formula is 0.1 or more, a crystal phase having a crystal structure other than the specific layered rock salt type crystal structure is easily formed in the positive electrode active material, which may lead to a decrease in discharge capacity.

[0022] The values ​​of b, c and f in the composition formula, that is, the molar ratio of the total number of moles of Ni, Mn or O relative to Li, Ni, Mn, W, Mg and O, are respectively in the range satisfying the relationship. When the values ​​of b, c and f in the composition formula do not satisfy the relationship, a crystalline phase having a crystalline structure other than the specific layered rock salt type crystalline structure is easily formed in the positive electrode active material, which may lead to a decrease in discharge capacity.

[0023] From the viewpoint of ensuring excellent thermal stability and output characteristics and further improving the discharge capacity, the value of b in the composition formula is preferably greater than 0.5 and less than 0.6. That is, the positive electrode active material preferably has a composition formula of Li a Ni b Mn c W d Mg e O f (wherein a to f in the composition formula satisfy the following relationships: 0.9<a<1.2, 0.5<b<0.6, 0.25<c<0.5, 0<d<0.06, 0<e<0.1, 1.9<f<2.1)

[0024] From the same viewpoint, the value of c in the composition formula is preferably greater than 0.25 and less than 0.42. That is, the positive electrode active material preferably has a composition formula Li a Ni b Mn c W d Mg e O f(wherein a to f in the composition formula satisfy the following relationships: 0.9 < a ​​< 1.2, 0.45 < b < 0.6, 0.25 < c < 0.42, 0 < d < 0.06, 0 < e < 0.1, 1.9 < f < 2.1) The positive electrode active material more preferably has a composition formula Li a Ni b Mn c W d Mg e O f (wherein a to f in the composition formula satisfy the following relationships: 0.9 < a ​​< 1.2, 0.5 < b < 0.6, 0.25 < c < 0.42, 0 < d < 0.06, 0 < e < 0.1, 1.9 < f < 2.1) The composition represented by the composition formula Li a Ni b Mn c W d Mg e O f (wherein a to f in the composition formula satisfy the following relationships: 0.9<a<1.2, 0.5<b<0.6, 0.25<c<0.42, 0.01<d<0.06, 0<e<0.08, 1.9<f<2.1)

[0025] The length of the a-axis in the lattice of the positive electrode active material is preferably Above and Below, the length of the c-axis is preferably Above and In this case, a positive electrode active material having excellent thermal stability and output characteristics can be obtained more reliably. From the same point of view, the positive electrode active material preferably has a crystal structure in which the half-value width w of the peak appearing in the diffraction angle range of 64.5±1° in the X-ray diffraction pattern obtained by the θ-2θ method is 64 The half-value width w of the peak appearing in the diffraction angle range of 44.4±1° 44 The ratio of w 64 / w 44 It is 1.10 or more and 1.30 or less.

[0026] In the range that does not impair the effect, the positive electrode active material may contain a crystalline phase having a crystal structure other than the specific layered rock salt type crystal structure. The content of the crystalline phase having a crystal structure other than the specific layered rock salt type crystal structure is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less.

[0027] It should be noted that the content of the crystalline phase in the positive electrode active material can be calculated based on the X-ray diffraction pattern obtained by powder X-ray diffraction. More specifically, the scanning range of the diffraction angle 2θ in the powder X-ray diffraction method is set to 10° to 90°, the scanning speed is set to 2° / minute, the sampling width is set to 0.02°, and the X-ray light source is set to CuKα rays. By performing Rietveld analysis based on the X-ray diffraction pattern obtained under such measurement conditions, the type of crystalline phase in the positive electrode active material can be identified, and the content of each crystalline phase can be calculated.

[0028] From the viewpoint of further shortening the diffusion distance of lithium ions in the positive electrode active material, the positive electrode active material is usually used in a powdered state. The positive electrode active material is preferably composed of particles with a particle size of 10 μm or less. That is, the positive electrode active material can be composed of primary particles having a particle size distribution with a maximum particle size of less than 10 μm, or it can be secondary particles formed by agglomeration of primary particles and having a particle size distribution with a maximum particle size of less than 10 μm. In this case, the diffusion distance of lithium ions in the positive electrode active material can be further shortened, and the internal resistance in the non-aqueous electrolyte secondary battery can be more easily reduced. From the viewpoint of further shortening the diffusion distance of lithium ions in the positive electrode active material, the positive electrode active material is preferably composed of primary particles with a particle size of less than 1 μm.

[0029] It should be noted that the particle size of the primary particles of the positive electrode active material can be measured based on an enlarged photograph obtained by observing the positive electrode active material using a scanning electron microscope (SEM). More specifically, for more than 50 particles of positive electrode active materials randomly selected from the enlarged photograph observed using SEM, the circumscribed circle for each particle is determined, and its diameter is used as the particle size of each particle. And, the maximum value of these particle sizes is used as the particle size of the positive electrode active material. In addition, the particle size of the secondary particles of the positive electrode active material can be measured using a particle size distribution measuring device using a laser scattering method.

[0030] (Method for producing positive electrode active material) As a method for manufacturing the positive electrode active material, for example, a solid phase method can be used. Specifically, a mixture of a compound as a Li source, a compound as a Ni source, a compound as a Mn source, a compound as a W source, and a compound as a Mg source is prepared, and the mixture is sintered under an oxidizing gas atmosphere. The ratio of each compound in the mixture can be appropriately set according to the composition formula of the crystalline phase in the desired positive electrode active material.

[0031] The mixture is preferably a powder. By making the mixture into a powder, each raw material compound can be evenly dispersed in the mixture. As a result, the unevenness of the composition of the sintered body after sintering can be further reduced, and the content rate of the crystalline phase can be further increased.

[0032] When preparing a powdery mixture, the raw material compound may be pulverized as necessary. As a pulverization method, manual pulverization using a mortar, mechanical pulverization using a ball mill or the like, etc. may be adopted.

[0033] In addition, when making a powdery mixture, the particle size of the mixture can also be adjusted by classifying the raw material compounds using a sieve or the like. By utilizing these methods to reduce the particle size of the mixture as much as possible, the raw material compounds can be dispersed more evenly. As a result, the unevenness of the composition of the sintered body after sintering can be further reduced, and the content rate of the crystalline phase can be further increased.

[0034] After the mixture is prepared, the mixture is fired in an oxidizing gas atmosphere to obtain a sintered body of the positive electrode active material containing the specific crystal phase. As the oxidizing gas, for example, air or the like can be used. The firing temperature during firing can be appropriately set within the range of 800° C. to 1100° C. The holding time during firing can be appropriately set within the range of 0.5 hours to 50 hours.

[0035] After the sintering is completed, the obtained sintered body is crushed to obtain a powdered positive electrode active material. The crushing method of the sintered body is not particularly limited. For example, various methods such as manual crushing using a mortar and mechanical crushing using a ball mill can be used as the crushing method. In addition, after the sintered body is crushed, the powder can be classified as needed to adjust the particle size of the positive electrode active material.

[0036] In addition, as a method for manufacturing the positive electrode active material, a coprecipitation method can be used. In the case of preparing the positive electrode active material by the coprecipitation method, for example, an alkaline reaction solution, a raw material solution, and an alkaline pH adjustment solution are prepared, wherein the raw material solution contains ions of two or more metal elements other than Li among the metal elements constituting the positive electrode active material. Then, while dripping the raw material solution containing the ions into the reaction solution, a pH adjustment solution is added to adjust the pH of the reaction solution after the raw material solution is added. Thus, a precursor containing the metal element is precipitated in the reaction solution. The concentration of each ion in the raw material solution can be appropriately set according to the composition formula of the desired crystalline phase in the positive electrode active material.

[0037] Next, the compound as a Li source and other raw materials added as needed are mixed with the precursor to prepare a mixture. By calcining the mixture under an oxidizing gas atmosphere, a sintered body of the positive electrode active material containing the specific crystalline phase can be obtained. As an oxidizing gas, for example, the atmosphere can be used. The calcination temperature during calcination can be appropriately set within the range of 800°C to 1100°C. The holding time during calcination can be appropriately set within the range of 0.5 hours to 50 hours.

[0038] After the sintering is completed, the obtained sintered body is crushed to obtain a powdered positive electrode active material. The crushing method of the sintered body is not particularly limited. For example, various methods such as manual crushing using a mortar and mechanical crushing using a ball mill can be used as the crushing method. In addition, after the sintered body is crushed, the powder can be classified as needed to adjust the particle size of the positive electrode active material.

[0039] In the method for producing the positive electrode active material, it is preferred that a precursor containing all metal elements in the composition except Li is prepared by a coprecipitation method, and the precursor is mixed with a compound containing Li to prepare a mixture. The positive electrode active material is obtained by firing the mixture in an oxidizing gas atmosphere.

[0040] In this way, by using the coprecipitation method to prepare a precursor containing all metal elements except Li, the distribution of each metal element in the precursor can be made more uniform. Then, after the precursor is mixed with a compound as a Li source, the mixture is calcined, thereby obtaining a more homogeneous positive electrode active material. Moreover, according to this method, the discharge capacity, output characteristics and thermal stability of the positive electrode active material can be improved more evenly.

[0041] In the case of making a precursor comprising all metal elements except Li by coprecipitation, the raw material solution added dropwise to the reaction solution can be one or more. However, depending on the combination of the compound dissolved in the raw material solution, sometimes a certain compound is difficult to dissolve in the raw material solution, and it is difficult to adjust the ratio of the metal element in the precursor to a desired range. From the viewpoint of more reliably avoiding this problem, it is preferred to prepare more than two raw material solutions. By preparing more than two raw material solutions, the compound comprising the metal element can be easily dissolved in each raw material solution. As a result, it is possible to more easily adjust the ratio of the metal element in the precursor to a desired range.

[0042] When two or more raw material solutions are prepared, for example, after dropping the other raw material solution into any one raw material solution, the raw material solution can be dropped into the reaction solution. More specifically, when preparing the precursor, a reaction solution showing alkalinity, a first raw material solution containing W, and a second raw material solution containing metal elements other than Li and W in the composition can be prepared. The first raw material solution is dropped into the second raw material solution to prepare a mixed solution, and then the mixed solution is dropped into the reaction solution to prepare the precursor.

[0043] In addition, for example, all the raw material solutions may be simultaneously added dropwise to the reaction solution. More specifically, when preparing the precursor, a reaction solution exhibiting alkalinity, a first raw material solution containing W, and a second raw material solution containing metal elements other than Li and W in the composition may be prepared. The first raw material solution and the second raw material solution are simultaneously added dropwise to the reaction solution to prepare the precursor.

[0044] Furthermore, in addition to the raw material solution and the reaction solution, an alkaline pH adjustment solution may be prepared, and the pH adjustment solution may be added dropwise to the reaction solution together with the first raw material solution, the second raw material solution, or the mixed solution to produce the precursor. In this case, the change in pH of the reaction solution accompanying the addition of the raw material solution can be suppressed, and a precursor having a desired composition can be generated more reliably.

[0045] (Non-aqueous electrolyte secondary battery) The positive electrode active material is used for non-aqueous electrolyte secondary batteries, and is particularly suitable for lithium ion secondary batteries. The secondary battery may include a positive electrode containing the positive electrode active material, a negative electrode, a separator, a non-aqueous electrolyte, additives, and a shell for accommodating them as main components. The shape of the secondary battery includes, for example, a coin-shaped, cylindrical, stacked, rectangular, and the like.

[0046] The positive electrode of the secondary battery has a positive electrode active material and a positive electrode current collector for holding the positive electrode active material. As the positive electrode current collector, for example, metal foils such as copper foil, aluminum foil, and nickel foil; various conductors such as stainless steel mesh, perforated metal, expanded metal, and metal mesh can be used.

[0047] The positive electrode may contain a binder between the positive electrode active material and the positive electrode current collector. As the binder, for example, fluorine-containing resins such as polyvinylidene fluoride, polytetrafluoroethylene, and fluororubber; and thermoplastic resins such as polypropylene, polyethylene, and polyethylene terephthalate can be used.

[0048] In addition, the positive electrode may contain a conductive agent or a conductive auxiliary agent for improving conductivity. As the conductive agent, for example, graphite, carbon black, acetylene black, cokes, etc. can be used.

[0049] The positive electrode can be produced, for example, by the following method. First, a paste-like positive electrode mixture containing a positive electrode active material is produced. In the positive electrode mixture, an organic solvent for dispersing or dissolving solid components such as the positive electrode active material can be included as needed. Next, the positive electrode mixture is applied to the surface of the positive electrode collector and then dried to form a positive electrode active material layer on the surface of the positive electrode collector. After the positive electrode active material layer is formed, the positive electrode active material layer can be pressurized as needed to increase the density of the positive electrode active material layer. Through the above, a positive electrode can be obtained.

[0050] The negative electrode of the secondary battery has a negative electrode active material and a negative electrode current collector for holding the negative electrode active material. As the negative electrode active material, for example, carbon materials having a graphite structure such as graphite and hard carbon, lithium titanate (Li4Ti5O 12 ) and other lithium-based oxides. In addition, as the negative electrode current collector, the same conductor as the positive electrode current collector can be used.

[0051] The negative electrode may contain a binder, a conductive agent, and a conductive auxiliary agent similarly to the positive electrode. The binder, conductive agent, and conductive auxiliary agent that can be used for the negative electrode are the same as those for the positive electrode.

[0052] The method for making the negative electrode is the same as that for the positive electrode. That is, first, a paste-like negative electrode mixture containing a negative electrode active material is made. The negative electrode mixture may contain an organic solvent for dispersing or dissolving solid components such as the negative electrode active material as needed. Next, the negative electrode mixture is applied to the surface of the negative electrode current collector and dried to form a negative electrode active material layer on the surface of the negative electrode current collector. After the negative electrode active material layer is formed, the negative electrode active material layer may be pressurized as needed to increase the density of the negative electrode active material layer. Through the above, a negative electrode can be obtained.

[0053] The non-aqueous electrolyte may contain an organic solvent and an electrolyte containing a lithium salt. As the lithium salt, for example, LiPF6 can be cited. In addition, the organic solvent may be set to at least one selected from the group consisting of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate. These organic solvents have high polarity and can dissolve electrolytes in large quantities. Therefore, by making these organic solvents into non-aqueous electrolytes for use, the migration number of charge carriers such as lithium ions in the secondary battery can be easily increased. Example

[0054] The positive electrode active material and the non-aqueous electrolyte secondary battery having the positive electrode active material are described in detail below. The positive electrode active material of this example has a composition formula of Lia Ni b Mn c W d Mg e O f (wherein a to f in the composition formula satisfy the following relationships: 0.9<a<1.2, 0.45<b<0.6, 0.25<c<0.5, 0<d<0.06, 0<e<0.1, 1.9<f<2.1) The positive electrode active material has a layered rock salt type crystal structure that can be attributed to the space group R-3m.

[0055] Specifically, the positive electrode active material (test materials S1 to S9) in this example has the composition shown in Table 1. It should be noted that test materials R1 to R8 in Table 1 are positive electrode active materials for comparison with test materials S1 to S9. The method for preparing the positive electrode active material in this example is described below.

[0056] (Test material S1) 200 mL of distilled water was added to a 2 L reaction container, and sodium hydroxide was dissolved to prepare a reaction solution with a pH of 12. Separately from the reaction solution, a raw material solution in which nickel sulfate and manganese sulfate were dissolved in distilled water, and a pH adjustment solution in which a sodium hydroxide aqueous solution and ammonia water were mixed were prepared.

[0057] Next, the reaction solution was heated to 50° C. While the temperature of the reaction solution was maintained, the raw material solution and the pH adjustment solution were simultaneously added dropwise to the reaction solution while stirring the reaction solution, thereby precipitating a precursor containing Ni and Mn in the reaction solution.

[0058] The precursor thus obtained is mixed with LiOH as a Li source, WO3 as a W source, and MgO as a Mg source to prepare a mixture. The mixture is calcined at a temperature of 950°C for 5 hours in the atmosphere, and then annealed at a temperature of 700°C for 12 hours to obtain a bulk positive electrode active material. The bulk positive electrode active material is crushed using a mortar to obtain a powdered positive electrode active material (test material S1). It should be noted that the positive electrode active material prepared by the described method is recorded with the symbol "M1" in the "Preparation Method" column of Table 1.

[0059] (Test materials R1 to R3) Test materials R1 to R3 have the same constitution as test material S1 except that at least one element of W and Mg is not contained. The method for preparing test materials R1 to R3 is the same as the method for preparing test material S1 except that WO3 and / or MgO are not added to the precursor.

[0060] (Test materials S2 to S9) 200 mL of distilled water was added to a 2 L reaction container, and sodium hydroxide was dissolved to prepare a reaction solution with a pH of 12. Separately from the reaction solution, a first raw material solution prepared by dissolving ammonium tungstate in distilled water, a second raw material solution prepared by dissolving nickel sulfate, manganese sulfate, and magnesium sulfate in distilled water, and a pH adjustment solution prepared by mixing a sodium hydroxide aqueous solution with aqueous ammonia were prepared.

[0061] Next, the reaction solution was heated to 50° C. While the temperature of the reaction solution was maintained, the first raw material solution, the second raw material solution, and the pH adjustment solution were simultaneously added dropwise to the reaction solution while stirring the reaction solution, thereby precipitating a precursor containing Ni, Mn, W, and Mg in the reaction solution.

[0062] Next, LiOH as a Li source is mixed with the precursor to prepare a mixture. The mixture is calcined at a temperature of 950°C for 5 hours in the atmosphere, and then annealed at a temperature of 700°C for 12 hours to obtain a bulk positive electrode active material. The bulk positive electrode active material is crushed using a mortar to obtain a powdered positive electrode active material (test materials S2 to S9). It should be noted that the positive electrode active material prepared by the method described is recorded with the symbol "M2" in the "Preparation Method" column of Table 1.

[0063] (Test materials R4 to R8) Test materials R4 to R8 have the same constitution as test materials S2 to S9 except that at least one element of W and Mg is not contained. The preparation method of test materials R4 to R8 is the same as the preparation method of test materials S2 to S9 except that WO3 and / or MgO are not added to the precursor.

[0064] Next, the compositions and crystal structures of the test materials S1 to S9 and the test materials R1 to S8 were identified.

[0065] Composition of positive electrode active material The molar ratio of each metal element in the positive electrode active material was measured by inductively coupled plasma atomic emission spectroscopy (ICP-AES). The composition of each test material when the molar ratio of oxygen atoms was set to 2 is shown in the "Composition of positive electrode active material" column of Table 1.

[0066] Crystal structure of positive electrode active material The crystal structure of the positive electrode active material was identified and the lattice constant was determined by powder X-ray diffraction. As an X-ray diffraction device, "SmartLab (registered trademark)" manufactured by Rigaku Co., Ltd. was used, and the characteristic X-ray irradiation was set to CuKα rays. In addition, the scanning range of the diffraction angle 2θ was set to 10° to 90°, the scanning speed was set to 2° / min, and the sampling width was set to 0.02°.

[0067] Based on the obtained X-ray diffraction pattern, the crystal structure of the positive electrode active material was identified. As a result, test materials S1 to S9 and test materials R1 to R8 all have a layered rock salt type crystal structure that can be attributed to space group R-3m. Table 1 shows the length of the a-axis and the length of the c-axis in the lattice of each positive electrode active material. In addition, Table 2 shows the content of the layered rock salt type crystal structure in each positive electrode active material, and the half-value width w of the peak that appears in the range of diffraction angle 64.5±1° 64 The half-value width w of the peak appearing in the diffraction angle range of 44.4±1° 44 The ratio of 64 / w 44 .

[0068] ·Composition and manufacturing method of secondary battery for evaluation Next, a non-aqueous electrolyte secondary battery (test battery) was prepared using the obtained positive electrode active material. Figure 1 As shown, the nonaqueous electrolyte secondary battery 1 of this example is a CR2032 type button battery including a positive electrode 2 , a negative electrode 3 , a separator 4 , and a nonaqueous electrolyte 5 .

[0069] More specifically, the secondary battery 1 includes a case 11 having a bottomed cylindrical shape and a relatively small height, and an upper cover 12 that closes the opening of the case 11. A space is formed between the case 11 and the upper cover 12. The upper cover 12 is joined to the case 11 by riveting.

[0070] The positive electrode 2, the negative electrode 3, the separator 4, and the non-aqueous electrolyte 5 are accommodated in the space between the shell 11 and the upper cover 12. A rubber seal (the original Japanese text of "seal": パッキン) 15 is arranged between the positive electrode 2 and the separator 4. In addition, a gasket 13 and a washer 14 are provided between the upper cover 12 and the positive electrode 2. The gasket 13 is arranged in a manner of abutting against the positive electrode 2. The washer 14 is arranged between the gasket 13 and the upper cover 12. Specifically, the gasket 13 of this example is a disc-shaped stainless steel plate.

[0071] The positive electrode 2 has a positive electrode current collector 21 and a positive electrode active material layer 22, wherein the positive electrode active material layer 22 contains any one of the positive electrode active materials shown in Table 1 and is disposed on the positive electrode current collector 21. Specifically, the positive electrode current collector 21 of this example is a disc-shaped aluminum foil with a diameter of 16 mm. Specifically, the negative electrode 3 is a disc-shaped metal lithium foil.

[0072] The separator 4 is made of polypropylene and is interposed between the positive electrode 2 and the negative electrode 3. The nonaqueous electrolyte 5 is filled at least between the positive electrode 2 and the negative electrode 3 in the secondary battery 1. Specifically, the nonaqueous electrolyte 5 of this example includes an ethylene carbonate-based organic solvent containing LiPF6 at a concentration of 1 mol / L.

[0073] Next, a method for manufacturing the secondary battery 1 is described. First, a positive electrode active material, graphite as a conductive aid, and polyvinylidene fluoride as a binder are mixed in a mass ratio of positive electrode active material: conductive aid: binder = 85:10:5 to obtain a positive electrode mixture. The positive electrode mixture is applied to the positive electrode current collector 21 to form a positive electrode active material layer 22. The thickness of the positive electrode active material layer 22 immediately after application is set to about 220 μm.

[0074] Next, the positive electrode active material layer 22 on the positive electrode current collector 21 was pressed at a pressure of about 100 MPa. The positive electrode active material layer 22 and the positive electrode current collector 21 were then punched out into a disk shape with a diameter of 16 mm to obtain the positive electrode 2. In addition, the negative electrode 3 was prepared by punching out lithium foil into a disk shape.

[0075] Next, the negative electrode 3, the separator 4, the seal 15, the positive electrode 2, the gasket 13, and the washer 14 are sequentially stacked in the case 11, and the non-aqueous electrolyte 5 is injected into the case 11. Then, the upper cover 12 is overlapped with the opening of the case 11 and riveted, thereby sealing the space between the case 11 and the upper cover 12. Thus, the secondary battery 1 is obtained.

[0076] Next, the obtained battery was used to measure the discharge capacity and evaluate the output characteristics. Note that a charge-discharge device ("BCS-815" manufactured by Bio-Logic) was used for the discharge capacity measurement and the output characteristics evaluation.

[0077] Discharge capacity measurement First, the secondary battery was charged in a constant current mode at a temperature of 25°C. The current density in the constant current mode was set to 11 mA / g, and the charge termination voltage was set to 4.5 V. After the charging was completed, the battery was discharged to 2.5 V at a constant current density of 11 mA / g, and the discharge curve at this time was obtained. Based on the discharge curve obtained in this way, the discharge capacity of the secondary battery was calculated. Table 2 shows the discharge capacity of the secondary battery using each positive electrode active material.

[0078] Evaluation of output characteristics After adjusting the open circuit voltage (i.e., OCV) of the secondary battery to 4.4V, the secondary battery is discharged at a discharge current equivalent to 5C (specifically, about 10mA), and the voltage of the secondary battery during discharge is measured. Then, the potential difference between the voltage of the secondary battery 0.1 seconds after the start of discharge and the voltage of the secondary battery 10 seconds after the start of discharge is divided by the discharge current, thereby calculating the DC resistance of the secondary battery. The value of the DC resistance of the secondary battery calculated in this way is shown in the "DC resistance" column of Table 2.

[0079] Evaluation of thermal stability First, the secondary battery was charged in a constant current-constant voltage mode at a temperature of 25° C. The current density in the constant current mode was set to 11 mA / g. In addition, the charge end voltage in the constant voltage mode was set to 4.5 V, and an appropriate charging current was passed to maintain the charge end voltage after 5 hours from the time when the voltage of the secondary battery reached the charge end voltage.

[0080] The secondary battery after charging was disassembled in a glove box filled with argon atmosphere, and the positive electrode was taken out. The positive electrode was washed with dimethyl carbonate and dried in the glove box. The positive electrode active material layer was collected from the dried positive electrode and subjected to differential scanning calorimetry analysis. It should be noted that the conditions of differential scanning calorimetry analysis are as follows.

[0081] Measurement start temperature: room temperature Measurement end temperature: 500°C Heating rate: 10℃ / min

[0082] Table 2 shows the peak temperature of the exothermic peak appearing in the DSC curve obtained by differential scanning calorimetry and the amount of heat released at the exothermic peak.

[0083] [Table 1]

[0084] [Table 2]

[0085] As shown in Table 1, test materials S1 to S8 have the composition represented by the specific composition formula and have a layered rock salt type crystal structure represented by space group R-3m. Therefore, as shown in Table 2, these test materials have excellent thermal stability and output characteristics.

[0086] In contrast, the test material R1, which has the same Ni content as the test materials S1 to S8 and does not contain both W and Mg, has a higher DC resistance and poorer output characteristics than the test materials S1 to S8. In addition, the test material R1 has a larger heat release and poorer thermal stability than the test materials S1 to S8.

[0087] The content of Ni is similar to that of test materials S1 to S8, and test material R2, which does not contain Mg, has a lower exothermic peak temperature than test materials S1 to S8, and there is a risk of decomposition at a relatively low temperature. In addition, test material R2 has a large exothermic heat and poor thermal stability.

[0088] The content of Ni was about the same as that of the test materials S1 to S8, and the test material R4 which did not contain Mg released more heat than the test materials S1 to S8 and had inferior thermal stability.

[0089] The content of Ni was about the same as that of the test materials S1 to S8, and the test materials R3 and R5 which did not contain W had higher DC resistance and inferior output characteristics than the test materials S1 to S8.

[0090] In addition, the test material S9 has a composition represented by the specific composition formula and has a layered rock salt type crystal structure represented by the space group R-3m. Therefore, the test material S9 has excellent thermal stability and output characteristics.

[0091] In contrast, the content of Ni is about the same as that of the test material S9, and the test material R6 that does not contain both W and Mg has a higher DC resistance and poorer output characteristics than the test material S9. In addition, the exothermic peak temperature of the test material R6 is lower than that of the test material S9, and there is a risk of decomposition at a relatively low temperature. In addition, the heat release of the test material R6 is large and the thermal stability is poor.

[0092] The content of Ni was about the same as that of the test material S9, and the test material R7 which did not contain Mg released more heat than the test material S9 and had inferior thermal stability.

[0093] The test material R8, which has a Ni content similar to that of the test material S9 and does not contain W, has a higher DC resistance and inferior output characteristics than the test material S9.

[0094] As described above, from the comparison of test materials S1 to S8 with test materials R1 to R5 having the same Ni content, and from the comparison of test material S9 with test materials R6 to R8, it can be understood that by adding both W and Mg to the Li-Ni-Mn-based positive electrode active material, the discharge capacity, output characteristics and thermal stability can be improved in a well-balanced manner.

[0095] The specific configurations of the positive electrode active material and the nonaqueous electrolyte secondary battery of the present invention are not limited to the configurations of the above-described embodiments, and can be appropriately modified within a range not impairing the gist of the present invention.

Claims

1. A positive electrode active material for a non-aqueous electrolyte secondary battery, characterized in that: The positive electrode active material has a composition formula of Li a Ni b Mn c W d Mg e O f The composition represented by, wherein a to f in the composition formula satisfy the following relationship: 0.9<a<1.2, 0.45<b<0.6, 0.25<c<0.5, 0<d<0.06, 0<e<0.1, 1.9<f<2.1, and The positive electrode active material has a layered rock salt type crystal structure that can be attributed to the space group R-3m.

2. The positive electrode active material according to claim 1, wherein The length of the a-axis in the lattice of the positive electrode active material is Above and Below, the length of the c-axis is Above and the following.

3. A non-aqueous electrolyte secondary battery, characterized in that: It has a positive electrode, a negative electrode and a non-aqueous electrolyte. The positive electrode comprises the positive electrode active material according to claim 1 or 2.

4. The method for producing a positive electrode active material according to claim 1 or 2, characterized in that: A precursor containing all the metal elements in the composition except Li is prepared by a coprecipitation method, The precursor is mixed with a compound containing Li to prepare a mixture, The positive electrode active material is obtained by calcining the mixture in an oxidizing gas atmosphere.

5. The method for producing a positive electrode active material according to claim 4, wherein: When preparing the precursor, an alkaline reaction solution, a first raw material solution containing W, and a second raw material solution containing metal elements other than Li and W in the composition are prepared. The first raw material solution and the second raw material solution are simultaneously added dropwise to the reaction solution to prepare the precursor.

6. The method for producing a positive electrode active material according to claim 5, wherein: When preparing the precursor, an alkaline pH adjustment solution is also prepared. The pH adjustment solution is added dropwise to the reaction solution together with the first raw material solution and the second raw material solution to prepare the precursor.

Citation Information

Patent Citations

  • Positive electrode active material for nonaqueous electrolyte secondary battery

    JP2012043637A